Development and experiment of a 60 kW horizontal-axis marine current power system. (August 2015) - Xu, Quan-kun; Liu, Hong-wei; Lin, Yong-gang; Yin, Xiu-xing; Li, Wei; Gu, Ya-jing
Abstract: A 60 kW horizontal-axis marine current power system is designed, built and tested to provide potentially cost-competitive electrical power for residents in remote islands. This power system mainly consists of a three-bladed marine current turbine, a drive-train system, power electronics and a control console. The turbine blade parameters are reasonably calculated and optimized based on the blade element momentum theory. The hydrodynamic performances of this turbine are predicted over a wide range of operating conditions. An adequate drive-train system is carefully designed to make the marine power system work smoothly and quietly even under harsh marine current conditions. The control console is also developed to facilitate the condition monitoring and generator power and speed regulations for this power system by adequately controlling the onshore power electronics. This power system has been tested under real marine current conditions to thoroughly evaluate its dynamic characteristics and effectiveness. Highlights: A 60°kW horizontal-axis marine current power system is designed, built and tested. Detailed design procedure and experimental data are provided. Experimental results demonstrate high power convention efficiency of the system.